The model of organic fertilizer adoption in urban farming to support environmentally friendly agriculture in Pekanbaru City, Riau Province, Indonesia - Marliati; Vaulina, Sisca; Dewi, Ilma Satriana; Dewi, Dian Chintya (Asian Journal of Agriculture and Rural Development, 2025)
This study examines farmer characteristics, urban farming profiles, levels of organic fertilizer adoption, and the factors influencing its adoption in Pekanbaru City. The degradation of agricultural land in Indonesia, including Pekanbaru, is primarily attributed to excessive chemical fertilizers, which compromise soil fertility and endanger food security. Although interest in organic farming is growing, its adoption remains limited due to inadequate government support, market challenges, and farmers’ dependence on chemical fertilizers for immediate results. Using a survey method targeting vegetable farmers who have used organic fertilizers for at least one year, the data were analyzed with Partial Least Square (PLS) modeling. The findings indicate that farmers, predominantly male (72.09%) with low educational attainment, face challenges such as limited land availability. Although farmers hold positive perceptions of organic fertilizers, especially chicken manure, they prefer chemical fertilizers due to their immediate impact. Moreover, agricultural extension services and government support for organic fertilizer adoption are deemed insufficient. The decision to adopt organic fertilizers is significantly influenced by land size, the performance of agricultural extension workers, and marketing strategies. To improve adoption rates, it is imperative to enhance agricultural extension services, optimize government support, and establish accessible marketing strategies, thereby promoting sustainable urban agriculture in Pekanbaru.